2017
DOI: 10.1088/1361-6587/aa7358
|View full text |Cite
|
Sign up to set email alerts
|

Generation of disc-like plasma from laser-matter interaction in the presence of a strong external magnetic field

Abstract: Dynamics of laser produced plasma in a strong magnetic field was studied using a 1 MA pulsed power generator coupled to an intense, high-energy laser. A 2-2.5 MG magnetic field was generated on the surface of a rod load 0.8-1.2 mm in diameter. A sub-nanosecond laser pulse with intensity of 3×10 15 W cm −2 was focused on the rod load surface. Side-on laser diagnostics showed the generation of two collimated jets 1-3 mm long on the front and rear sides of the load. End-on laser diagnostics reveal that the lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…2 b,c). This global morphology is consistent with previous observations 30 , 31 , 33 , 34 . Extending these previous studies, we can observe in Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2 b,c). This global morphology is consistent with previous observations 30 , 31 , 33 , 34 . Extending these previous studies, we can observe in Fig.…”
Section: Resultssupporting
confidence: 93%
“…4 and 10 of that paper). In stark contrast, when applying the external magnetic field, we observe that the plasma is focused on axis by the magnetic tension into a conical shape, from which emerges a slab 33 , 34 which is observed by the optical (Fig. 2 b,c) and X-ray diagnostics (see Fig.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…We note that the configuration in which a plasma stream propagates across a magnetic field has long been experimentally investigated (see e.g., Sucov et al 1967;Bruneteau et al 1970;Plechaty et al 2013;García-Rubio et al 2016;Ivanov et al 2017;Tang et al 2018;Khiar et al 2019;Leal et al 2020;Filippov et al 2021). The most recent studies Plechaty et al (2013), García-Rubio et al (2016), Ivanov et al (2017), Tang et al (2018), Khiar et al (2019), and Leal et al (2020), investigated the overall plasma dynamics in such a configuration and revealed that the plasma is able to extend along the magnetic field with a plasma slab-like global morphology, where the plasma is being compressed by the magnetic field into a thin layer in the plane that contains the magnetic field. The specificity of our work with respect to the abovementioned studies is that here the surface of the target affected by laser irradiation is very large.…”
Section: Introductionmentioning
confidence: 98%